2022
DOI: 10.1021/jacs.2c07967
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Thione-Derived Perylene Diimides and Their Bio-Conjugation for Simultaneous Imaging, Tracking, and Targeted Photodynamic Therapy

Abstract: In this study, the chromophore 3,4,9,10-perylenetetracarboxylic diimide (PDI) is anchored with phenyl substituents at the imide N site, followed by thionation, yielding a series of thione products 1S-PDI-D, 2S-cis-PDI-D, 2S-trans-PDI-D, 3S-PDI-D, and 4S-PDI-D, respectively, with n = 1, 2, 3, and 4 thione. The photophysical properties are dependent on the number of anchored thiones, where the observed prominent lower-lying absorption is assigned to the S 0 → S 2 (ππ*) transition and is red-shifted upon increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 60 publications
8
35
0
Order By: Relevance
“…In aqueous solution, BTI , T1 , T2 , and T3 showed the propensity to form nanoaggregates ( BTI = 316 nm, T1 = 100 nm, T2 = 172 nm, T3 = 151 nm) in line with previously published data reporting on the use of thionaphthalimides 37 or thione-derived perylene diimides 41 as activated-self-assembled PSs (Supplementary Fig. 20 ).…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…In aqueous solution, BTI , T1 , T2 , and T3 showed the propensity to form nanoaggregates ( BTI = 316 nm, T1 = 100 nm, T2 = 172 nm, T3 = 151 nm) in line with previously published data reporting on the use of thionaphthalimides 37 or thione-derived perylene diimides 41 as activated-self-assembled PSs (Supplementary Fig. 20 ).…”
Section: Resultssupporting
confidence: 89%
“…20 ). It is important to note that the propensity of self-assembled dyes to disaggregate into monomeric units upon binding to biological targets in cell culture conditions has been used in both biosensing 54 57 and therapeutic applications 37 , 41 , 58 . This would be a particularly important expected feature in the present study, as we already mentioned that no singlet-oxygen or other ROS generation could be monitored in aqueous media, while singlet oxygen and superoxide generation could be attested in chloroform and DMSO, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This photosensitisation process can be achieved using site-selectively modified nucleobases or synthetic chromophores with heavy-atom-free thiocarbonyl functionalities. [7][8][9][10] Given the long lifetime and high energy of the triplet excited states, thiocarbonyl chromophores also display photocatalytic activities comparable to common organometallic photocatalysts. 11 For materials applications, Seferos and co-workers reported that the carrier mobility of n-type organic field-effect transistors (OFET) based on perylene diimide derivatives can be enhanced by thionation.…”
Section: Introductionmentioning
confidence: 99%